The insertion of Primary Health Care in the teaching-learning process: integrative review (Research, Society and Development, 2020)
The approach of training in health courses, since the beginning of the academic experience, with the reality of health manifested in our country, determines the creation of a space for the production of knowledge and reflection on the Brazilian Health System. Objective: this study aimed to show the pedagogical proposal conducted by the service-learning in the Primary Health Care interface as a tool for the training of health professionals. Methodology: the methodological path was an integrative review in the databases of the United States National Library of Medicine (PubMed), Virtual Health Library (BVS) and “Scientific Electronic Library Online” (SciELO). Results: after reading and analyzing the publications, the results were characterized for two categories in the study: “Primary Health Care: human resources and the scenario for professional training” and “Pedagogical strategy: academic training in line with service-learning”. Final considerations: the hegemony of hospital care and mechanistic processes still transit the training of health professionals. Primary Health Care provides a practical and transformative environment for academic training and although it has recognized limitations the potentialities must be defended and valued, increasing the scenario as a training object.